Clinicopathological features of desmoplastic small round cell tumors: clinical series and literature review - Ling-Ling Wang (World Journal of Surgical Oncology, 2021)
Abstract Background and purpose Desmoplastic small round cell tumor (DSRCT) is a highly malignant sarcoma that occurs in the abdominopelvic cavities of adolescents. The accurate diagnosis of DSRCT is challenging owing to limited literatures. Our study aimed to investigate the relationship between clinicopathological features and prognosis in patients with DSRCTs. Methods Data of 8 patients with DSRCT originating from the abdominal cavity were retrospectively reviewed. The clinical manifestations, pathological characteristics, treatment approaches, and prognosis were analyzed. The histopathological (identified using hematoxylin-eosin staining), immunohistochemical, and molecular diagnostic (using fluorescence in situ hybridization) features were also reviewed. Results All patients were male aged between 24 and 45 years (median age, 30 years). The main clinical symptoms included abdominal distension, abdominal pain, and constipation. Seven of the 8 patients developed metastases to either distant organs or lymph nodes. Multiple gray nodules with diameters of 1–10 cm and poorly defined boundaries were scattered throughout the omentum and mesentery. Histopathological examination demonstrated well-defined nests composed of small round blue cells separated by markedly desmoplastic stroma. Immunohistochemical analysis revealed positive expressions of desmin, vimentin and C-terminal of Wilm’s tumor suppressor (WT-1). The Ewing sarcoma breakpoint region 1 gene fused with WT1 (EWSR1-WT1) gene fusion was detected in all patients. Cytoreductive surgery (CRS) was performed in 6 patients. Follow-up period ranged from 7.5 to 28.5 months with a median of 17.2 months. Three patients died during follow-up. Conclusion DSRCT is highly aggressive and presents distinctive morphological features. CRS is the essential therapy for DSRCT. A test for the combined expression of desmin, cytokeratins, and C-terminal of WT-1, as well as the analysis of morphologic features, might be helpful during DSRCT diagnosis, and the EWSR1-WT1 gene fusion is the gold standard for definitive diagnosis. Our work will provide new insights into the diagnosis and treatment of DSRCTs.